Methodology for Assessing the Lithium-Sulfur Battery Degradation for Practical Applications. (7th July 2017) - Knap, Vaclav; Stroe, Daniel Ioan; Purkayastha, Rajlakshmi; Walus, Sylwia; Auger, Daniel J; Fotouhi, Abbas; Propp, Karsten
Abstract : Lithium-Sulfur (Li-S) battery is an emerging battery technology receiving growing amount of attention due to its potential high contributions of gravimetric energy density, safety and low production cost. However, there are still some obstacles preventing their swift commercialization. Li-S batteries are driven by different electrochemical processes than commonly used Lithium-ion batteries, which often results in their very different behavior. Therefore, the modelling and testing have to be adjusted to reflect this unique behavior to prevent possible biases. A methodology for a reference performance test for the Li-S batteries is proposed in this study to point out the Li-S battery features and provide guidance to users how to deal with them and possible results into standardization.